A soil structure improver and a method of preparing the same

CN121674075BActive Publication Date: 2026-10-23INSTITUTE OF ENVIRONMENT AND SUSTAINABLE DEVELOPMENT IN AGRICULTURE CAAS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511748242.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-10-23
Estimated Expiration
2045-11-26

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种土壤结构改良剂及其制备方法,以解决上述背景技术提出的土壤持水能力差的技术问题

Benefits of technology

1、通过构建高孔隙率的无机-有机杂化包覆层(蒙脱石与二氧化硅形成立体骨架,有机相提供亲水羧基),并利用交联网络锁住水分,大幅增加土壤饱和含水率,减少水分渗漏与蒸发。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121674075B_ABST
    Figure CN121674075B_ABST
Patent Text Reader

Abstract

The application discloses a soil structure modifier and a preparation method thereof, and relates to the technical field of soil modifiers. The method uses refined biochar obtained by pyrolysis and acid washing of corn stalks as a base material, first carries out hybrid coating and crosslinking on the base material together with inorganic phases containing montmorillonite and fumed silicon dioxide and organic phases containing sodium acrylate and the like to construct a stable porous framework structure, then carries out activation, sequentially grafts acrylic acid-beta-hydroxyethyl ester and the like to form a primary product, and carries out copolymerization with methylacryloyloxyethyl trimethylammonium chloride modified chitosan and the like, and finally the modifier is prepared. Through synergistic action of inorganic-organic hybrid coating and multiple grafting modification, the specific surface area, porosity and hydrophilic group density of the modifier are significantly improved, and the binding force of the modifier with soil particles is enhanced, so that the water holding capacity of soil is significantly improved and long-acting and stable water retention is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soil conditioner technology, specifically to a soil structure conditioner and its preparation method. Background Technology

[0002] Soil water-holding capacity is a core soil physicochemical property for maintaining agricultural production and ecosystem stability. It directly determines soil water resource utilization and plant growth suitability, and is a key foundation for ensuring crop yields and promoting ecological restoration. However, due to the combined effects of multiple factors such as irrational farming practices, land use structure changes, climate change, and environmental pollution, the degradation of soil water-holding capacity is becoming increasingly prominent globally, and has become a significant bottleneck restricting sustainable agricultural development, exacerbating water scarcity, and threatening ecological stability.

[0003] Soil types vary across different regions, and the problem of insufficient soil water-holding capacity exhibits significant regional characteristics and has a wide impact. In arid and semi-arid regions, rainfall is scarce and unevenly distributed, resulting in poor soil water and fertilizer retention capacity, severe waste of irrigation water resources, and high water evaporation rates. The contradiction between water scarcity and insufficient soil water-holding capacity is particularly prominent, directly limiting the scale of local agricultural production and crop yields. In high-altitude and cold regions, changes in land use patterns easily lead to soil structure damage and reduced porosity, thereby decreasing key indicators such as maximum soil water holding capacity, capillary water holding capacity, and field water holding capacity. This not only affects crop growth but also weakens the soil's water conservation function, threatening the stability of high-altitude ecosystems. In farmland areas that have been cultivated for a long time, unreasonable planting and cultivation patterns easily lead to soil compaction, reduced organic matter content, increased soil bulk density, and imbalanced pore structure, causing a continuous decline in soil water storage and retention capacity, further exacerbating agricultural production's dependence on irrigation. From the perspective of agricultural production as a whole, insufficient soil water-holding capacity has become an important reason for crop yield reduction and low agricultural water resource utilization efficiency. Meanwhile, soil water-holding capacity is closely related to key physicochemical properties such as soil pore structure, organic matter content, soil texture, and bulk density. External factors such as vegetation cover, climate conditions, and topographic features also indirectly affect soil water-holding capacity by influencing soil structure. The interaction and imbalance of these factors further exacerbate the complexity and difficulty of remediation of soil water-holding capacity degradation.

[0004] Therefore, developing a soil structure improver that can specifically optimize soil structure and has a stable water retention effect is of great practical significance and application value for solving the current technical problem of insufficient soil water holding capacity, improving the efficiency of agricultural water resource utilization, and ensuring food security and sustainable development of the ecological environment. Summary of the Invention

[0005] The purpose of this invention is to provide a soil structure improver and its preparation method to solve the technical problem of poor soil water retention capacity mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a soil structure modifier includes the following steps: S1. Take corn stalks, dry them, crush them and sieve them. Pyrolyze the sieve material under nitrogen protection, cool it and crush it and sieve it again to obtain crude biochar. Add the crude biochar to hydrochloric acid solution to soak and stir, wash it with deionized water until neutral, and dry it to obtain refined biochar substrate. S2. Add montmorillonite nanosheets and fumed silica to deionized water, then add silane coupling agent KH-570, mix and ultrasonically disperse to obtain an inorganic phase dispersion. S3. Add sodium acrylate, hydroxypropyl methylcellulose, and N-vinylpyrrolidone to deionized water, stir until dissolved, then add potassium persulfate-sodium bisulfite composite initiator, purge with nitrogen to remove air, preheat and keep warm to initiate prepolymerization, and obtain organic phase prepolymer liquid. S4. Add the refined biochar substrate to the inorganic phase dispersion and stir. Then slowly add the organic phase prepolymer solution. After the addition is complete, add the crosslinking agent ethylene glycol diglycidyl ether and continue the reaction. After the reaction is complete, cool, centrifuge, wash, and dry to obtain hybrid coated modified biochar. S5. Take the hybrid coated modified biochar and add it to deionized water, add hydrogen peroxide solution and ferrous sulfate, activate it by ultrasound, filter it, wash it until neutral, and dry it to obtain the activated hybrid coated modified biochar. S6. Add the activated hybrid coated modified biochar to deionized water, add β-hydroxyethyl acrylate and polyethylene glycol diacrylate, purge with nitrogen to remove air, heat up and add ammonium persulfate-sodium bisulfite composite initiator, stir the reaction to obtain the primary graft product. S7. Add deionized water to the primary grafting product system, add methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 2-acrylamide-2-methylpropanesulfonic acid, and then add sodium dihydrogen phosphate-disodium hydrogen phosphate buffer to maintain the pH of the system. After heating, add ammonium persulfate, stir the reaction, and after the reaction is completed, cool it. Wash it with deionized water and ethanol solution in sequence, and finally wash it with deionized water until there is no ethanol residue. After drying, crush and sieve to obtain the soil structure improver.

[0007] In this invention, the soil conditioner synergistically enhances soil water retention capacity in two ways. Firstly, by constructing a highly porosity and stable inorganic-organic hybrid coating layer on the surface of refined biochar, soil water retention capacity is improved through both physical storage and preliminary adsorption. Montmorillonite nanosheets (layered porous structure) in the inorganic phase synergistically form a three-dimensional support framework with fumed silica (high specific surface area nanoparticles), significantly increasing the specific surface area and pore number of the modified biochar, providing ample physical storage space for soil moisture. The organic phase prepolymer, carrying a large number of hydrophilic carboxyl groups, tightly binds with the inorganic phase and biochar substrate, adsorbing free water and capillary water in the soil through intermolecular forces, reducing water leakage. Furthermore, the three-dimensional network structure formed by the crosslinking agent further locks in the water within the pores, slowing down natural evaporation and ultimately significantly increasing the soil's saturated moisture content, laying a solid foundation for long-term water retention. On the other hand, by grafting β-hydroxyethyl acrylate onto hybrid coated modified biochar, hydrophilic groups such as hydroxyl and ester groups are introduced, which complement the hydrophilic carboxyl groups of the hybrid coating layer, further expanding the water adsorption capacity and improving water retention stability. In addition, the modified chitosan quaternary ammonium salt grafted onto the hybrid coated modified biochar enhances the binding force between the amendment and soil particles through electrostatic interaction, preventing the amendment from migrating with water. The sulfonic acid group of 2-acrylamide-2-methylpropanesulfonic acid has strong hydrophilicity and can deeply adsorb water in the soil. The grafted structure formed by these two types of groups not only ensures the efficient adsorption of water by the soil, but also allows for the slow release of water according to the needs of crop growth, reducing ineffective evaporation and seepage, and significantly increasing the water content most easily utilized by crops, thus achieving long-term stable maintenance of soil moisture.

[0008] Preferably, in step S1, the pyrolysis temperature is 550–560°C and the pyrolysis time is 2–3 hours.

[0009] Preferably, in step S2, the mass ratio of montmorillonite nanosheets to fumed silica is 12:(2-4).

[0010] Preferably, in step S3, the mass ratio of sodium acrylate to hydroxypropyl methylcellulose is 10:(3-5).

[0011] Preferably, in step S4, trehalose is also added to the inorganic phase dispersion.

[0012] In the technical solution of this invention, the research and development team discovered through in-depth research that the cations on the chitosan modified with methacryloyloxyethyltrimethylammonium chloride will competitively exchange and adsorb with the cations in the montmorillonite interlayer, preferentially occupying the ion exchange sites, thereby inhibiting the water absorption and swelling performance of montmorillonite, resulting in the interlayer water storage space not being fully expanded. At the same time, it weakens the hydrogen bonding force between montmorillonite and water, significantly reducing the water holding contribution of montmorillonite, and ultimately weakening the synergistic water holding efficiency of both aspects. To further address this technical problem, this invention adsorbs and binds trehalose onto hybrid coated modified biochar. Trehalose is a structurally stable, non-reducing disaccharide that does not react with the inorganic or organic monomers or crosslinking agents in the first modification system, and does not interfere with the free radical polymerization reaction of the second grafting, exhibiting extremely strong compatibility. Its molecules can be rapidly adsorbed onto the surface and interlayer of montmorillonite nanosheets via hydrogen bonds, forming an ultrathin protective film. This protective film neither occupies the ion exchange sites of montmorillonite nor affects the inorganic-organic phase interface bonding, and can effectively prevent excessive exchange between the cationic groups on the methacryloyloxyethyltrimethylammonium chloride-modified chitosan and the interlayer cations of montmorillonite, thereby ensuring the water absorption and swelling properties and interlayer water storage function of montmorillonite, restoring and enhancing the synergistic water retention effect of both aspects.

[0013] Preferably, the amount of trehalose added is (5-10) wt% of the refined biochar substrate.

[0014] Preferably, in step S6, the mass ratio of the activated hybrid coated modified biochar to β-hydroxyethyl acrylate is 10:(5-8).

[0015] Preferably, in step S7, the preparation method of methacryloyloxyethyltrimethylammonium chloride-modified chitosan includes the following steps: Chitosan was dissolved in acetic acid solution to obtain a chitosan solution. Then, methacryloxyethyltrimethylammonium chloride and ammonium persulfate were added. Nitrogen gas was passed through to purge air, and the mixture was heated to react. After washing and drying, methacryloxyethyltrimethylammonium chloride-modified chitosan was obtained.

[0016] Preferably, in step S7, the mass ratio of methacryloxyethyltrimethylammonium chloride-modified chitosan to 2-acrylamide-2-methylpropanesulfonic acid is 5:(1-2).

[0017] A soil structure modifier is prepared by the above method. Compared with the prior art, the beneficial effects of the present invention are: 1. By constructing a high-porosity inorganic-organic hybrid coating layer (montmorillonite and silica form a three-dimensional framework, and the organic phase provides hydrophilic carboxyl groups), and using a cross-linked network to lock in moisture, the soil saturated water content is greatly increased, and water leakage and evaporation are reduced.

[0018] 2. By grafting polymers containing hydrophilic groups such as hydroxyl, ester, and sulfonic acid groups onto the hybrid coating layer, the water adsorption capacity is further expanded. The binding of the amendment to soil particles is strengthened through electrostatic interaction, preventing migration with water and achieving slow water release to maintain easily usable water for crops for a long time.

[0019] 3. By adding trehalose to protect the montmorillonite structure, the subsequent cationic components are prevented from inhibiting its water absorption and swelling properties, ensuring the synergistic effect of the montmorillonite interlayer water storage function and the overall water retention effect, thereby improving the overall performance stability of the modifier. Attached Figure Description

[0020] Figure 1 This is a SEM image of the surface of the soil structure modifier prepared in Example 1 of the present invention. Detailed Implementation

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1 A method for preparing a soil structure modifier includes the following steps: Step 1: Take 20g of corn stalks and dry them in a 60℃ forced-air drying oven for 12h. After taking them out, crush them with a high-speed pulverizer and pass them through an 80-mesh standard sieve. Put the sieve material into a tube furnace and heat it to 555℃ at a heating rate of 5℃ / min under nitrogen protection (inlet rate 1L / min). Pyrolyze it at a constant temperature for 2.5h. After cooling to room temperature, crush it again and pass it through a 300-mesh standard sieve to obtain crude biochar. Add the crude biochar to a 1.5mol / L hydrochloric acid solution (solid-liquid ratio 1:10g / mL) and soak it at room temperature for 3h. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Place the product in a 90℃ vacuum drying oven and dry it for 5h to obtain refined biochar substrate.

[0023] Step 2: Take 12g of montmorillonite nanosheets and 3.5g of fumed silica and add them to 90mL of deionized water. Then add 0.8g of silane coupling agent KH-570. Place the mixture in a 30℃ constant temperature water bath and ultrasonically disperse it at 400W for 40min. During this period, adjust the pH of the system to 4.0-4.5 with dilute hydrochloric acid to obtain an inorganic phase dispersion.

[0024] Step 3: Take 10g of sodium acrylate, 4.5g of hydroxypropyl methylcellulose, and 0.4g of N-vinylpyrrolidone and add them to 50mL of deionized water. Stir at 300r / min at 25℃ until completely dissolved. Then add 0.15g of potassium persulfate-sodium bisulfite composite initiator (mass ratio 1:1). Purge the system with nitrogen gas (at a rate of 0.5L / min) to remove air from the system. Preheat the system to 35℃ and keep it at that temperature for 15min to initiate the monomer prepolymerization reaction and obtain the organic phase prepolymer liquid.

[0025] Step 4: Add 10g of refined biochar substrate and 0.8g of trehalose to the above inorganic phase dispersion, and mechanically stir at 400r / min for 150min at 30℃. Then, raise the temperature of the system to 65℃, adjust the pH to 8.5 with 1mol / L sodium hydroxide solution, and slowly add 50g of organic phase prepolymer liquid dropwise at a rate of 1.5mL / min through a constant pressure dropping funnel. Immediately after the addition is complete, add 0.3g of crosslinking agent ethylene glycol diglycidyl ether, maintain the temperature at 65℃ and the stirring rate at 400r / min and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge the product (5000r / min, 10min), wash it 3 times with deionized water, and finally dry it in a vacuum drying oven at 70℃ for 9h to obtain hybrid coated modified biochar.

[0026] Step 5: Add 10g of hybrid coated modified biochar to 60mL of deionized water, adjust the pH of the system to 3.0 with 1mol / L hydrochloric acid, then add 3g of 30% hydrogen peroxide solution and 0.8g of ferrous sulfate. Place the system in a 35℃ constant temperature water bath and activate it with 300W ultrasonication for 25min. After the reaction is complete, filter and collect the solid product, wash it with deionized water until neutral, and dry it in an 80℃ drying oven for 4h to obtain the activated hybrid coated modified biochar.

[0027] Step 6: Add 10g of activated hybrid coated modified biochar to 50mL of deionized water, adjust the pH of the system to 8.0 with 1mol / L sodium hydroxide solution, then add 7g of β-hydroxyethyl acrylate and 2.5g of polyethylene glycol diacrylate, purge air with nitrogen at a rate of 0.8L / min, heat the system to 55℃, add 0.2g of ammonium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), stir the reaction at a rate of 250r / min for 3.5h to obtain the primary grafted product.

[0028] Step 7: Add 5g of chitosan to 100mL of 1.5% acetic acid solution and stir at 250r / min for 30min at 30℃ until completely dissolved to obtain a chitosan solution; add 8g of methacryloxyethyltrimethylammonium chloride and 0.06g of ammonium persulfate to the solution, purge with nitrogen at a rate of 0.6L / min to remove air, heat the system to 70℃, and stir at a constant temperature for 5h; after the reaction is completed, cool to room temperature, pour the product into 200mL of anhydrous ethanol to precipitate, filter to collect the solid, wash 3 times with anhydrous ethanol and 2 times with acetone, and then dry in a vacuum drying oven at 75℃ for 6h to obtain methacryloxyethyltrimethylammonium chloride modified chitosan.

[0029] Add 10 mL of deionized water to the primary grafting product system, then add 5 g of methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 1.85 g of 2-acrylamide-2-methylpropanesulfonic acid. Add 20 mL of 0.1 mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate buffer (pH=6.5) to maintain the pH of the system. Heat the sealed system to 65 °C, add 0.15 g of ammonium persulfate, and continue the reaction for 4.5 h while maintaining a stirring rate of 250 r / min. After the reaction is complete, cool to room temperature and wash three times with deionized water and twice with 50% ethanol solution. Finally, wash with deionized water until no ethanol residue remains in the washing liquid. Place the product in an 80 °C vacuum drying oven and dry for 7 h. After removal, pulverize with a high-speed pulverizer and pass through a 110-mesh standard sieve to obtain the soil structure improver.

[0030] Example 2 A method for preparing a soil structure modifier includes the following steps: Step 1: Take 20g of corn stalks and dry them in a 60℃ forced-air drying oven for 12h. After taking them out, crush them with a high-speed pulverizer and pass them through an 80-mesh standard sieve. Put the sieve material into a tube furnace and heat it to 555℃ at a heating rate of 5℃ / min under nitrogen protection (inlet rate 1L / min). Pyrolyze it at a constant temperature for 2.5h. After cooling to room temperature, crush it again and pass it through a 300-mesh standard sieve to obtain crude biochar. Add the crude biochar to a 1.5mol / L hydrochloric acid solution (solid-liquid ratio 1:10g / mL) and soak it at room temperature for 3h. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Place the product in a 90℃ vacuum drying oven and dry it for 5h to obtain refined biochar substrate.

[0031] Step 2: Take 12g of montmorillonite nanosheets and 2.5g of fumed silica and add them to 90mL of deionized water. Then add 0.8g of silane coupling agent KH-570. Place the mixture in a 30℃ constant temperature water bath and disperse it using 400W ultrasonication for 40min. During this period, adjust the pH of the system to 4.0-4.5 with dilute hydrochloric acid to obtain an inorganic phase dispersion.

[0032] Step 3: Take 10g of sodium acrylate, 3.5g of hydroxypropyl methylcellulose, and 0.4g of N-vinylpyrrolidone and add them to 50mL of deionized water. Stir at 300r / min at 25℃ until completely dissolved. Then add 0.15g of potassium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), purge with nitrogen gas (rate 0.5L / min) to remove air from the system, preheat the system to 35℃ and keep it at that temperature for 15min to initiate the monomer prepolymerization reaction and obtain the organic phase prepolymer liquid.

[0033] Step 4: Add 10g of refined biochar substrate and 0.6g of trehalose to the above inorganic phase dispersion, and mechanically stir at 400r / min for 150min at 30℃. Then, raise the temperature of the system to 65℃, adjust the pH to 8.5 with 1mol / L sodium hydroxide solution, and slowly add 50g of organic phase prepolymer liquid dropwise at a rate of 1.5mL / min through a constant pressure dropping funnel. Immediately after the addition is complete, add 0.3g of crosslinking agent ethylene glycol diglycidyl ether, maintain the temperature at 65℃ and the stirring rate at 400r / min and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge the product (5000r / min, 10min), wash it 3 times with deionized water, and finally dry it in a vacuum drying oven at 70℃ for 9h to obtain hybrid coated modified biochar.

[0034] Step 5: Add 10g of hybrid coated modified biochar to 60mL of deionized water, adjust the pH of the system to 3.0 with 1mol / L hydrochloric acid, then add 3g of 30% hydrogen peroxide solution and 0.8g of ferrous sulfate. Place the system in a 35℃ constant temperature water bath and activate it with 300W ultrasonication for 25min. After the reaction is complete, filter and collect the solid product, wash it with deionized water until neutral, and dry it in an 80℃ drying oven for 4h to obtain the activated hybrid coated modified biochar.

[0035] Step 6: Add 10g of activated hybrid coated modified biochar to 50mL of deionized water, adjust the pH of the system to 8.0 with 1mol / L sodium hydroxide solution, then add 6g of β-hydroxyethyl acrylate and 2.5g of polyethylene glycol diacrylate, purge air with nitrogen at a rate of 0.8L / min, heat the system to 55℃, add 0.2g of ammonium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), stir the reaction at a rate of 250r / min for 3.5h to obtain the primary grafted product.

[0036] Step 7: Add 5g of chitosan to 100mL of 1.5% acetic acid solution and stir at 250r / min for 30min at 30℃ until completely dissolved to obtain a chitosan solution; add 8g of methacryloxyethyltrimethylammonium chloride and 0.06g of ammonium persulfate to the solution, purge with nitrogen at a rate of 0.6L / min to remove air, heat the system to 70℃, and stir at a constant temperature for 5h; after the reaction is completed, cool to room temperature, pour the product into 200mL of anhydrous ethanol to precipitate, filter to collect the solid, wash 3 times with anhydrous ethanol and 2 times with acetone, and then dry in a vacuum drying oven at 75℃ for 6h to obtain methacryloxyethyltrimethylammonium chloride modified chitosan.

[0037] Add 10 mL of deionized water to the primary grafting product system, then add 5 g of methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 1.32 g of 2-acrylamide-2-methylpropanesulfonic acid. Add 20 mL of 0.1 mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate buffer (pH=6.5) to maintain the pH of the system. Heat the sealed system to 65 °C, add 0.15 g of ammonium persulfate, and continue the reaction for 4.5 h while maintaining a stirring rate of 250 r / min. After the reaction is complete, cool to room temperature and wash three times with deionized water and twice with 50% ethanol solution. Finally, wash with deionized water until no ethanol residue remains in the washing liquid. Place the product in an 80 °C vacuum drying oven and dry for 7 h. After removal, pulverize with a high-speed pulverizer and pass through a 110-mesh standard sieve to obtain the soil structure improver.

[0038] Example 3 A method for preparing a soil structure modifier includes the following steps: Step 1: Take 20g of corn stalks and dry them in a 60℃ forced-air drying oven for 12h. After taking them out, crush them with a high-speed pulverizer and pass them through an 80-mesh standard sieve. Put the sieve material into a tube furnace and heat it to 555℃ at a heating rate of 5℃ / min under nitrogen protection (inlet rate 1L / min). Pyrolyze it at a constant temperature for 2.5h. After cooling to room temperature, crush it again and pass it through a 300-mesh standard sieve to obtain crude biochar. Add the crude biochar to a 1.5mol / L hydrochloric acid solution (solid-liquid ratio 1:10g / mL) and soak it at room temperature for 3h. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Place the product in a 90℃ vacuum drying oven and dry it for 5h to obtain refined biochar substrate.

[0039] Step 2: Take 12g of montmorillonite nanosheets and 3g of fumed silica and add them to 90mL of deionized water. Then add 0.8g of silane coupling agent KH-570. Place the mixture in a 30℃ constant temperature water bath and ultrasonically disperse it at 400W for 40min. During this period, adjust the pH of the system to 4.0-4.5 with dilute hydrochloric acid to obtain an inorganic phase dispersion.

[0040] Step 3: Take 10g of sodium acrylate, 4g of hydroxypropyl methylcellulose, and 0.4g of N-vinylpyrrolidone and add them to 50mL of deionized water. Stir at 300r / min at 25℃ until completely dissolved. Then add 0.15g of potassium persulfate-sodium bisulfite composite initiator (mass ratio 1:1). Purge the system with nitrogen gas (at a rate of 0.5L / min) to remove air from the system. Preheat the system to 35℃ and keep it at that temperature for 15min to initiate the monomer prepolymerization reaction and obtain the organic phase prepolymer liquid.

[0041] Step 4: Add 10g of refined biochar substrate and 0.7g of trehalose to the above inorganic phase dispersion, and mechanically stir at 400r / min for 150min at 30℃. Then, raise the temperature of the system to 65℃, adjust the pH to 8.5 with 1mol / L sodium hydroxide solution, and slowly add 50g of organic phase prepolymer liquid dropwise at a rate of 1.5mL / min through a constant pressure dropping funnel. Immediately after the addition is complete, add 0.3g of crosslinking agent ethylene glycol diglycidyl ether, maintain the temperature at 65℃ and the stirring rate at 400r / min and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge the product (5000r / min, 10min), wash it 3 times with deionized water, and finally dry it in a vacuum drying oven at 70℃ for 9h to obtain hybrid coated modified biochar.

[0042] Step 5: Add 10g of hybrid coated modified biochar to 60mL of deionized water, adjust the pH of the system to 3.0 with 1mol / L hydrochloric acid, then add 3g of 30% hydrogen peroxide solution and 0.8g of ferrous sulfate. Place the system in a 35℃ constant temperature water bath and activate it with 300W ultrasonication for 25min. After the reaction is complete, filter and collect the solid product, wash it with deionized water until neutral, and dry it in an 80℃ drying oven for 4h to obtain the activated hybrid coated modified biochar.

[0043] Step 6: Add 10g of activated hybrid coated modified biochar to 50mL of deionized water, adjust the pH of the system to 8.0 with 1mol / L sodium hydroxide solution, then add 6.5g of β-hydroxyethyl acrylate and 2.5g of polyethylene glycol diacrylate, purge the air with nitrogen gas at a rate of 0.8L / min, heat the system to 55℃, add 0.2g of ammonium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), stir the reaction at a rate of 250r / min for 3.5h to obtain the primary grafted product.

[0044] Step 7: Add 5g of chitosan to 100mL of 1.5% acetic acid solution and stir at 250r / min for 30min at 30℃ until completely dissolved to obtain a chitosan solution; add 8g of methacryloxyethyltrimethylammonium chloride and 0.06g of ammonium persulfate to the solution, purge with nitrogen at a rate of 0.6L / min to remove air, heat the system to 70℃, and stir at a constant temperature for 5h; after the reaction is completed, cool to room temperature, pour the product into 200mL of anhydrous ethanol to precipitate, filter to collect the solid, wash 3 times with anhydrous ethanol and 2 times with acetone, and then dry in a vacuum drying oven at 75℃ for 6h to obtain methacryloxyethyltrimethylammonium chloride modified chitosan.

[0045] Add 10 mL of deionized water to the primary grafting product system, then add 5 g of methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 1.56 g of 2-acrylamide-2-methylpropanesulfonic acid. Add 20 mL of 0.1 mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate buffer (pH=6.5) to maintain the pH of the system. Heat the sealed system to 65 °C, add 0.15 g of ammonium persulfate, and continue the reaction for 4.5 h while maintaining a stirring rate of 250 r / min. After the reaction is complete, cool to room temperature and wash three times with deionized water and twice with 50% ethanol solution. Finally, wash with deionized water until no ethanol residue remains in the washing liquid. Place the product in an 80 °C vacuum drying oven and dry for 7 h. After removal, pulverize with a high-speed pulverizer and pass through a 110-mesh standard sieve to obtain the soil structure improver.

[0046] Example 4 A method for preparing a soil structure modifier includes the following steps: Step 1: Take 20g of corn stalks and dry them in a 60℃ forced-air drying oven for 12h. After taking them out, crush them with a high-speed pulverizer and pass them through an 80-mesh standard sieve. Put the sieved material into a tube furnace and heat it to 560℃ at a rate of 5℃ / min under nitrogen protection (inlet rate 1L / min). Pyrolyze it at a constant temperature for 3h. After cooling to room temperature, crush it again and pass it through a 300-mesh standard sieve to obtain crude biochar. Add the crude biochar to a 1.5mol / L hydrochloric acid solution (solid-liquid ratio 1:10g / mL) and soak it at room temperature for 3h. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Place the product in a 90℃ vacuum drying oven and dry it for 5h to obtain refined biochar substrate.

[0047] Step 2: Take 12g of montmorillonite nanosheets and 4g of fumed silica and add them to 90mL of deionized water. Then add 0.8g of silane coupling agent KH-570. Place the mixture in a 30℃ constant temperature water bath and ultrasonically disperse it at 400W for 40min. During this period, adjust the pH of the system to 4.0-4.5 with dilute hydrochloric acid to obtain an inorganic phase dispersion.

[0048] Step 3: Add 10g sodium acrylate, 5g hydroxypropyl methylcellulose, and 0.4g N-vinylpyrrolidone to 50mL of deionized water and stir at 300r / min at 25℃ until completely dissolved. Then add 0.15g potassium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), purge with nitrogen gas (rate 0.5L / min) to remove air from the system, preheat the system to 35℃ and keep it at that temperature for 15min to initiate the monomer prepolymerization reaction and obtain the organic phase prepolymer liquid.

[0049] Step 4: Add 10g of refined biochar substrate and 1.0g of trehalose to the above inorganic phase dispersion, and mechanically stir at 400r / min for 150min at 30℃. Then, raise the temperature of the system to 65℃, adjust the pH to 8.5 with 1mol / L sodium hydroxide solution, and slowly add 50g of organic phase prepolymer liquid dropwise at a rate of 1.5mL / min through a constant pressure dropping funnel. Immediately after the addition is complete, add 0.3g of crosslinking agent ethylene glycol diglycidyl ether, maintain the temperature at 65℃ and the stirring rate at 400r / min and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge the product (5000r / min, 10min), wash it 3 times with deionized water, and finally dry it in a vacuum drying oven at 70℃ for 9h to obtain hybrid coated modified biochar.

[0050] Step 5: Add 10g of hybrid coated modified biochar to 60mL of deionized water, adjust the pH of the system to 3.0 with 1mol / L hydrochloric acid, then add 3g of 30% hydrogen peroxide solution and 0.8g of ferrous sulfate. Place the system in a 35℃ constant temperature water bath and activate it with 300W ultrasonication for 25min. After the reaction is complete, filter and collect the solid product, wash it with deionized water until neutral, and dry it in an 80℃ drying oven for 4h to obtain the activated hybrid coated modified biochar.

[0051] Step 6: Add 10g of activated hybrid coated modified biochar to 50mL of deionized water, adjust the pH of the system to 8.0 with 1mol / L sodium hydroxide solution, then add 8g of β-hydroxyethyl acrylate and 2.5g of polyethylene glycol diacrylate. Purge the air with nitrogen at a rate of 0.8L / min, heat the system to 55℃, add 0.2g of ammonium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), and stir the reaction at a rate of 250r / min for 3.5h to obtain the primary grafted product.

[0052] Step 7: Add 5g of chitosan to 100mL of 1.5% acetic acid solution and stir at 250r / min for 30min at 30℃ until completely dissolved to obtain a chitosan solution; add 8g of methacryloxyethyltrimethylammonium chloride and 0.06g of ammonium persulfate to the solution, purge with nitrogen at a rate of 0.6L / min to remove air, heat the system to 70℃, and stir at a constant temperature for 5h; after the reaction is completed, cool to room temperature, pour the product into 200mL of anhydrous ethanol to precipitate, filter to collect the solid, wash 3 times with anhydrous ethanol and 2 times with acetone, and then dry in a vacuum drying oven at 75℃ for 6h to obtain methacryloxyethyltrimethylammonium chloride modified chitosan.

[0053] Add 10 mL of deionized water to the primary grafting product system, then add 5 g of methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 2 g of 2-acrylamide-2-methylpropanesulfonic acid. Add 20 mL of 0.1 mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate buffer (pH=6.5) to maintain the pH of the system. Heat the sealed system to 65 °C, add 0.15 g of ammonium persulfate, and continue the reaction for 4.5 h while maintaining a stirring rate of 250 r / min. After the reaction is complete, cool to room temperature and wash three times with deionized water and twice with 50% ethanol solution. Finally, wash with deionized water until no ethanol residue remains in the washing liquid. Place the product in an 80 °C vacuum drying oven and dry for 7 h. After removal, pulverize with a high-speed pulverizer and pass through a 110-mesh standard sieve to obtain the soil structure improver.

[0054] Example 5 A method for preparing a soil structure modifier includes the following steps: Step 1: Take 20g of corn stalks and dry them in a 60℃ forced-air drying oven for 12h. After taking them out, crush them with a high-speed pulverizer and pass them through an 80-mesh standard sieve. Put the sieved material into a tube furnace and heat it to 550℃ at a rate of 5℃ / min under nitrogen protection (inlet rate 1L / min). Pyrolyze it at a constant temperature for 2h. After cooling to room temperature, crush it again and pass it through a 300-mesh standard sieve to obtain crude biochar. Add the crude biochar to a 1.5mol / L hydrochloric acid solution (solid-liquid ratio 1:10g / mL) and soak it at room temperature for 3h. Then wash it repeatedly with deionized water until the pH of the washing solution is neutral. Place the product in a 90℃ vacuum drying oven and dry it for 5h to obtain refined biochar substrate.

[0055] Step 2: Take 12g of montmorillonite nanosheets and 2g of fumed silica and add them to 90mL of deionized water. Then add 0.8g of silane coupling agent KH-570. Place the mixture in a 30℃ constant temperature water bath and ultrasonically disperse it at 400W for 40min. During this period, adjust the pH of the system to 4.0-4.5 with dilute hydrochloric acid to obtain an inorganic phase dispersion.

[0056] Step 3: Add 10g sodium acrylate, 3g hydroxypropyl methylcellulose, and 0.4g N-vinylpyrrolidone to 50mL of deionized water and stir at 300r / min at 25℃ until completely dissolved. Then add 0.15g potassium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), purge with nitrogen gas (rate 0.5L / min) to remove air from the system, preheat the system to 35℃ and keep it at that temperature for 15min to initiate the monomer prepolymerization reaction and obtain the organic phase prepolymer liquid.

[0057] Step 4: Add 10g of refined biochar substrate and 0.5g of trehalose to the above inorganic phase dispersion, and mechanically stir at 400r / min for 150min at 30℃. Then, raise the temperature of the system to 65℃, adjust the pH to 8.5 with 1mol / L sodium hydroxide solution, and slowly add 50g of organic phase prepolymer liquid dropwise at a rate of 1.5mL / min through a constant pressure dropping funnel. After the addition is complete, immediately add 0.3g of crosslinking agent ethylene glycol diglycidyl ether, maintain the temperature at 65℃ and the stirring rate at 400r / min and continue the reaction for 2h. After the reaction is completed, cool to room temperature, centrifuge the product (5000r / min, 10min), wash it 3 times with deionized water, and finally dry it in a vacuum drying oven at 70℃ for 9h to obtain hybrid coated modified biochar.

[0058] Step 5: Add 10g of hybrid coated modified biochar to 60mL of deionized water, adjust the pH of the system to 3.0 with 1mol / L hydrochloric acid, then add 3g of 30% hydrogen peroxide solution and 0.8g of ferrous sulfate. Place the system in a 35℃ constant temperature water bath and activate it with 300W ultrasonication for 25min. After the reaction is complete, filter and collect the solid product, wash it with deionized water until neutral, and dry it in an 80℃ drying oven for 4h to obtain the activated hybrid coated modified biochar.

[0059] Step 6: Add 10g of activated hybrid coated modified biochar to 50mL of deionized water, adjust the pH of the system to 8.0 with 1mol / L sodium hydroxide solution, then add 5g of β-hydroxyethyl acrylate and 2.5g of polyethylene glycol diacrylate, purge the air with nitrogen gas at a rate of 0.8L / min, heat the system to 55℃, add 0.2g of ammonium persulfate-sodium bisulfite composite initiator (mass ratio 1:1), stir the reaction at a rate of 250r / min for 3.5h to obtain the primary grafted product.

[0060] Step 7: Add 5g of chitosan to 100mL of 1.5% acetic acid solution and stir at 250r / min for 30min at 30℃ until completely dissolved to obtain a chitosan solution; add 8g of methacryloxyethyltrimethylammonium chloride and 0.06g of ammonium persulfate to the solution, purge with nitrogen at a rate of 0.6L / min to remove air, heat the system to 70℃, and stir at a constant temperature for 5h; after the reaction is completed, cool to room temperature, pour the product into 200mL of anhydrous ethanol to precipitate, filter to collect the solid, wash 3 times with anhydrous ethanol and 2 times with acetone, and then dry in a vacuum drying oven at 75℃ for 6h to obtain methacryloxyethyltrimethylammonium chloride modified chitosan.

[0061] Add 10 mL of deionized water to the primary grafting product system, then add 5 g of methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 1 g of 2-acrylamide-2-methylpropanesulfonic acid. Add 20 mL of 0.1 mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate buffer (pH=6.5) to maintain the pH of the system. Heat the sealed system to 65 °C, add 0.15 g of ammonium persulfate, and continue the reaction at a stirring rate of 250 r / min for 4.5 h. After the reaction is completed, cool to room temperature, wash three times with deionized water, wash twice with 50% ethanol solution, and finally wash with deionized water until there is no ethanol residue in the washing liquid. Place the product in an 80 °C vacuum drying oven and dry for 7 h. After removal, pulverize with a high-speed pulverizer and pass through a 110 mesh standard sieve to obtain the soil structure improver.

[0062] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that steps 2, 3 and 4 are omitted in the preparation of the soil structure conditioner, and the hybrid coated modified biochar in step 5 is replaced with refined biochar substrate.

[0063] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that steps 5, 6 and 7 are omitted in the preparation process of the soil structure conditioner. The soil structure conditioner is a hybrid coated modified biochar.

[0064] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that trehalose is not added to the inorganic phase dispersion in step 4 during the preparation of the soil structure conditioner.

[0065] Performance testing: 1. Soil saturated moisture content test: Weigh 2 kg of dry aeolian sand that has passed through a 2 mm sieve, add the prepared soil structure conditioner at a ratio of 1‰, mix well, and then add at 1.1 g / cm³. 3The bulk density was measured and placed in 15cm×20cm flowerpots, with three replicates per group. A control group of untreated sandy soil was also included. Water was slowly added to the flowerpots until visible water appeared on the soil surface. The soil was left to stand for 24 hours to allow for full water penetration and saturation. The entire flowerpot was then weighed, and the total mass at saturation was recorded. The soil was completely dried to constant weight and weighed again. The saturated moisture content was calculated using the formula: "Saturated moisture content (%) = (Total saturated mass - Total dried mass) / Dried soil mass × 100%". The average of the three replicates was taken as the final result. The test results are shown in Table 1.

[0066] 2. Crop Available Moisture Content Test: Using the same flowerpot samples as those tested for saturated moisture content, insert a tensiometer and place them outdoors to air dry naturally (ambient temperature 25-30℃, relative humidity 40-60%). Record the soil water potential daily at 8:00 AM. When the water potential reaches 80 kPa, determine the soil moisture content at this point using the weighing method. Calculate the result using the formula "Crop Available Moisture Content (%) = Saturated Moisture Content - Moisture Content at 80 kPa". This value reflects the total amount of water in the soil that can be directly absorbed and utilized by crops. Take the average of three replicates. The test results are shown in Table 1.

[0067] 3. Test for the content of water-stable aggregates larger than 0.25 mm: Soil samples that have completed the water-holding capacity test were allowed to continue outdoor natural curing for one month. After removing impurities such as stones and plant debris, 100 g of soil sample was weighed and determined using the mechanical wet sieving method: The sample was placed on a 2 mm standard sieve, rinsed with deionized water to remove fine soil, and then the remaining soil sample was transferred to a 0.25 mm standard sieve. The sieve surface was kept 5 cm above the water surface, and the sieve was moved up and down at a frequency of 30 times / min for 5 min. The aggregates remaining on the 0.25 mm sieve were collected and dried in a 60℃ drying oven to constant weight. The content of water-stable aggregates larger than 0.25 mm (%) was calculated using the formula "Mass of dried aggregates / Total mass of sample × 100%", and the average value of 3 replicates was taken. The test results are shown in Table 1.

[0068] 4. Soil moisture evaporation rate test: Soil samples containing the above-mentioned mixed amendment were tested at a rate of 1.1 g / cm³. 3 The bulk density was measured in a cylindrical container with a diameter of 10 cm and a height of 8 cm. Water was added to the saturated moisture content, and the container was placed in a constant temperature and humidity chamber (temperature 28℃, relative humidity 50%, wind speed 0.3 m / s). The mass change was recorded by weighing the container at the same time every day for 7 consecutive days. The average daily evaporation rate (g / d) was calculated using the formula "Daily average evaporation rate (g / d) = (initial saturated mass - mass on day 7) / 7". The average of three replicates was taken to reflect the long-term effectiveness of soil moisture retention. The test results are shown in Table 1.

[0069] Table 1:

[0070] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a soil structure conditioner, characterized in that, Includes the following steps: S1. Take corn stalks, dry them, crush them and sieve them. Pyrolyze the sieve material under nitrogen protection, cool it and crush it and sieve it again to obtain crude biochar. Add the crude biochar to hydrochloric acid solution to soak and stir, wash it with deionized water until neutral, and dry it to obtain refined biochar substrate. S2. Add montmorillonite nanosheets and fumed silica to deionized water, then add silane coupling agent KH-570, mix and ultrasonically disperse to obtain an inorganic phase dispersion. S3. Add sodium acrylate, hydroxypropyl methylcellulose, and N-vinylpyrrolidone to deionized water, stir until dissolved, then add potassium persulfate-sodium bisulfite composite initiator, purge with nitrogen to remove air, preheat and keep warm to initiate prepolymerization, and obtain organic phase prepolymer liquid. S4. Add the refined biochar substrate to the inorganic phase dispersion and stir. Then slowly add the organic phase prepolymer solution. After the addition is complete, add the crosslinking agent ethylene glycol diglycidyl ether and continue the reaction. After the reaction is complete, cool, centrifuge, wash, and dry to obtain hybrid coated modified biochar. S5. Take the hybrid coated modified biochar and add it to deionized water, add hydrogen peroxide solution and ferrous sulfate, activate it by ultrasound, filter it, wash it until neutral, and dry it to obtain the activated hybrid coated modified biochar. S6. Add the activated hybrid coated modified biochar to deionized water, add β-hydroxyethyl acrylate and polyethylene glycol diacrylate, purge with nitrogen to remove air, heat up and add ammonium persulfate-sodium bisulfite composite initiator, stir the reaction to obtain the primary graft product. S7. Add deionized water to the primary grafting product system, add methacryloyloxyethyltrimethylammonium chloride-modified chitosan and 2-acrylamide-2-methylpropanesulfonic acid, and then add sodium dihydrogen phosphate-disodium hydrogen phosphate buffer to maintain the pH of the system. After heating, add ammonium persulfate, stir the reaction, and after the reaction is completed, cool it. Wash it with deionized water and ethanol solution in sequence, and finally wash it with deionized water until there is no ethanol residue. After drying, crush and sieve to obtain the soil structure improver.

2. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S1, the pyrolysis temperature is 550–560°C and the pyrolysis time is 2–3 hours.

3. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S2, the mass ratio of montmorillonite nanosheets to fumed silica is 12:(2-4).

4. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S3, the mass ratio of sodium acrylate to hydroxypropyl methylcellulose is 10:(3-5).

5. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S4, trehalose is also added to the inorganic phase dispersion.

6. The method for preparing a soil structure conditioner according to claim 5, characterized in that, The amount of trehalose added is (5-10) wt% of the refined biochar substrate.

7. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S6, the mass ratio of the activated hybrid coated modified biochar to β-hydroxyethyl acrylate is 10:(5-8).

8. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S7, the preparation method of methacryloyloxyethyltrimethylammonium chloride-modified chitosan includes the following steps: Chitosan was dissolved in acetic acid solution to obtain a chitosan solution. Then, methacryloxyethyltrimethylammonium chloride and ammonium persulfate were added. Nitrogen gas was passed through to purge air, and the mixture was heated to react. After washing and drying, methacryloxyethyltrimethylammonium chloride-modified chitosan was obtained.

9. The method for preparing a soil structure conditioner according to claim 1, characterized in that, In step S7, the mass ratio of methacryloyloxyethyltrimethylammonium chloride-modified chitosan to 2-acrylamide-2-methylpropanesulfonic acid is 5:(1-2).

10. A soil structure conditioner, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.

Citation Information

Patent Citations

  • Chitosan charcoal-based water retention material as well as preparation method and application thereof

    CN115873605A

  • Preparation method of biochar-loaded cellulose-grafted acrylic acid stabilized nano-iron

    CN118929834A